An Inquiry-Creative Learning Model to Improve Students’ Critical Thinking Skills in Machining Engineering Instruction - H Mansur; Saiful Prayogi; Nova Kurnia (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
Abstract Vocational education in machining engineering often continues to emphasize the mastery of practical procedures, while students’ critical thinking skills in analysing problems, evaluating alternatives, and making technical decisions have not been optimally developed. This study aimed to examine the effectiveness of the Inquiry-Creative Learning model in improving students’ critical thinking skills and to identify the supporting and inhibiting factors in its implementation. The study employed a mixed-methods approach with an explanatory sequential design. The quantitative phase used a quasi-experimental pretest-posttest control group design involving 63 eleventh-grade students in the Machining Engineering Program, consisting of 30 students in the experimental group and 33 students in the control group. The qualitative phase involved six students from the experimental group and two mechanical engineering teachers through semi-structured interviews and observations. The test instrument measured four indicators of critical thinking, namely analysis, inference, evaluation, and decision-making. The data were analysed using descriptive statistics, gain, N-gain, ANOVA, Mann-Whitney U test, eta squared, and thematic analysis. The results showed that the mean score of the experimental group increased from 36.00 to 71.20, while that of the control group increased from 37.58 to 47.36. The N-gain score of the experimental group was 0.539, which was in the moderate category, whereas that of the control group was 0.145, which was in the low category. ANOVA showed significant differences in posttest scores (F = 157.207; p < 0.001; η² = 0.720), gain scores (F = 110.140; p < 0.001; η² = 0.644), and N-gain scores (F = 221.174; p < 0.001; η² = 0.784), which were further supported by the Mann-Whitney U test. The qualitative data revealed that group discussion, real problems, hands-on practice, availability of tools, and teacher readiness supported students’ critical thinking, whereas limited time, low self-confidence, and student passivity served as inhibiting factors. This study concludes that Inquiry-Creative Learning is effective in improving students’ critical thinking skills and has implications for vocational learning that is investigative, reflective, contextual, authentic, and collaborative.